Laro sa baga - Roño, Chito S.; Aquino, Angel; Morales, Carlos; Mina, Ara; Wilson, Monique; Gil, Mark; Picache, Cherry Pie 1970-; Escaño, Cholo; Reyes, Edgar; Barry, Malu (Regal Entertainment, Inc., 2000)
The movie is about Ding's inclination to answer all his sexual urges but eventually learns that nothing in the world of carnal desires is worth anything without the power of love. He develops an infatuation to his godmother/surrogate parent Carmen. Realizing that his infatuation is useless, he falls for Dee, Carmen's adopted daughter.